Dynamical Characteristics of the Linear Rolling Guide with Numerical Simulation and Experiment - Xiaopeng Li; Hao Guo; Jingnian Liu; Yali Liu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Research results will be different when the boundary condition is changed. In this work, the finite element model of the linear rolling guide of the NC machine tool is established. Then the natural frequencies and the corresponding vibration modals of the linear rolling guide model are obtained with two different boundary conditions. One boundary condition is that the movable joint surface of the linear rolling guide is considered, and regardless of the influence of the bolt joint surface of the guide. And another boundary condition is that the movable joint surface of the linear rolling guide and the influence of bolt joint surface of the guide are all considered. By comparing the modal characters of the two states, it is proved that the movable joint and bolted interfaces of the guide have certain effects on the dynamic performance of the linear rolling guide. For the experiment, the linear rolling guide also has been tested in two ways, the slider excited and the sliding guide excited respectively. Comparing the results obtained from numerical simulation and experiment, the validity of finite element model and the influence of the boundary conditions on the interface of the linear rolling guide are verified. This will help the dynamic analysis on the linear rolling guide and other research objects. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1920